A megakaryocyte morphological classification-based predictive model for steroid sensitivity in primary immune thrombocytopenia. (2nd October 2020) - Zhu, Jingjing; Chen, Rongrong; Zhao, Shuqi; Zhu, Lixia; Li, Xueying; Xie, Mixue; Ye, Xiujin
Abstract: The first-line therapy for primary immune thrombocytopenia (ITP) is steroids, but about one-third of patients do not respond to steroids. Recent studies have shown megakaryocyte (MK) growth and development abnormalities and poorly compensated thrombopoiesis. Here, we attempted to determine the impact of MK morphological classification on steroid response. We enrolled 170 adult patients with primary ITP and divided them into steroid-sensitive ITP (109/170) and non-steroid-sensitive ITP (61/170) groups. In the univariate logistic model, female, reduced thrombocytogenic MK count (TMC), increased granular MK count to total MK count ratio (GMC/TM ratio), and elevated naked nucleus MK count to TM count ratio were significantly associated with steroid-sensitive ITP. In the multivariate logistic model, sex, reduced TMC, and increased GMC/TM ratio were independent predictors of steroid-sensitive ITP diagnosis. Based on the regression parameters, we established a predictive index with weighted risk score of 1 assigned each to sex, TMC, and GMC/TM ratio. A predictive index ≥2 points had the best area under the curve value (0.63) with 47.7% sensitivity and 78.7% specificity for predicting steroid sensitivity. These findings may help guide early treatment strategies in ITP.